The Effective English Teacher: Perceptions from Student Teachers and Teacher Educators - Sahat Maringan Samosir; I-Chung Ke; Kresna Ningsih Manik (Journal of General Education and Humanities, 2025)
This study aimed to determine student teachers’ and teacher educators’ perceptions of an effective English teacher in terms of content, pedagogical, and personal knowledge in the English study program at Universitas Prima Indonesia (UNPRI). To achieve this objective, this study was designed as a mixed-methods study. To achieve this objective, this study was designed using a mixed method to look for the perceptions of 82 student teachers and 10 teacher educators. Data were collected through a 36-item Likert-type questionnaire and follow-up interviews. The results indicate that both groups agree that combining all the components is important for an effective teacher. Comparing both groups’ perceptions, the results showed a statistically significant difference (p ≤ 0.05) for 11 out of 36 items. It was found that student teachers place higher importance on some effective attributes than teacher educators do and vice versa. Additionally, the study found that pedagogical and personal knowledge was equally, if not more, important than content knowledge in defining an effective English teacher. This study highlights the significance of balancing content, pedagogical, and personal knowledge in teacher effectiveness, particularly in the EFL context of Indonesia, and discusses its pedagogical implications and limitations. This study was small due to a lack of participants. Future research should include more participants for comparison.